PERUMUSAN STRATEGI PEMASARAN MELALUI PENENTUAN PRIORITAS TRAPEZOIDAL FUZZY NUMBER (Studi Kasus Industri Minuman Tradisional) - Fajar Azzam Pasha Akhmad (Universitas Mitra Karya, 2019)
Competition in the industrial world is getting tighter along with the continuous increase in the industry growth rate. This competition has resulted in each industry being more observant in formulating its company's marketing strategy. PT. X is a traditional beverage industry that is on the Small and Medium Industry scale. The main problem in this industry is the limited funds to develop business and carry out marketing activities. Currently the industrial market growth is 16.67%, while the market share relative to the main competitors is 0.07. The Boston Consulting Group Matrix states that the company is in a question mark position. There are 13 variations offered to determine the priority of their interests by 7 experts. A total of 3 strategies were selected through the Trapezoidal Fuzzy Number, namely adding new markets through new product development (72.72), partnering in investment (71.50) and breaking into existing markets (70.93). The first strategy is formulated by developing packaging variations and product variations. The second strategy is formulated with the company's proactive attitude in seeking information about investors to establish cooperation in the field of investment with the company. The third strategy is formulated with the attitude and commitment of the company to ensure product availability and maintain product quality. ABSTRAK Persaingan di dunia industri semakin ketat seiring dengan terus meningkatnya laju pertumbuhan industri. Persaingan ini mengakibatkan setiap industri lebih jeli dalam merumuskan strategi pemasaran perusahaannya. PT. X merupakan industri minuman tradisional yang berada pada skala Industri Kecil Menengah. Permasalahan utama industri ini adalah terbatasnya dana untuk mengembangkan usaha dan menjalankan kegiatan pemasaran. Saat ini pertumbuhan pasar industri sebesar 16,67%, sedangkan pangsa pasar relatif terhadap pesaing utama adalah 0,07. Matriks Boston Consulting Group menyatakan bahwa perusahaan berada pada posisi tanda tanya. Terdapat 13 variasi yang ditawarkan untuk menentukan prioritas kepentingannya oleh 7 orang pakar. Sebanyak 3 strategi terpilih melalui Trapezoidal Fuzzy Number, yaitu menambah pasar baru melalui pengembangan produk baru (72,72), bermitra dalam investasi (71,50) dan menerobos pasar yang ada (70,93). Strategi pertama dirumuskan dengan mengembangkan variasi kemasan dan variasi produk. Strategi kedua dirumuskan dengan sikap proaktif perusahaan dalam mencari informasi mengenai investor untuk menjalin kerjasama dalam bidang investasi dengan perusahaannya. Strategi ketiga dirumuskan dengan sikap dan komitmen perusahaan untuk menjamin ketersediaan produk dan menjaga kualitas produk